THE PROSPECTS OF FORMING SOCIAL MARKET ECONOMY - M. E. Kosov (Финансы: теория и практика)
The development of economic relations is influenced not only by the productive forces but also by intangible values and institutions which interact with economic relations to create a strong positive impetus. The necessity and timeliness of the approaches in this perspective is explained, firstly, by the fact that structural development of the material productive forces in Russia is far from meeting the post-industrial society needs. Secondly, the existing social and economic system in Russia is actually a system of «peripheral capitalism» which is firmly rooted. The article is written on the base of dissertation research for the degree of Doctor in Economics.in social relations and public opinion and remains «a major impediment hampering Russia to use the historical chance to join the world of developed, sovereign, influential states» [1, p. 4].The article showcases the models for social and economic development of Russia; these models are built through integration of the fundamental assumptions that determine the long-term prospects of building a socially-oriented state. The modern institutionalization of dynamics of the economic relations in Russia in the field of distribution and consumption should be focused on overcoming the poverty of a large part of the population as well as an excessive polarization of incomes; on increasing the incentive function in the formation of incomes of various social strata and groups.